2002
DOI: 10.1016/s0925-4439(02)00165-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of expression of iron-metabolism genes in ceruloplasmin-deficient mice

Abstract: Aceruloplasminemia is an autosomal recessive disorder caused by mutations in the ceruloplasmin (CP) gene, and is characterized by a unique combination of neurovisceral iron overload and iron deficiency anemia. We generated CP-deficient (CP(-/-)) mice to investigate the functional involvement of CP in iron metabolism. The mice showed a marked iron overload in the liver and mild iron deficiency anemia. We examined the expression of iron-metabolism genes in the duodenum and liver using TaqMan RT-PCR. The divalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
44
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
8
44
1
1
Order By: Relevance
“…All of these observations are consistent with the model that copper status can modulate iron release due to the metal's regulation of FPN1 gene expression. This model is also consistent with the observations that copper-deficient rodents, which have ironloaded but copper-depleted livers, display profound microcytic anemia (5, 6), whereas Cp Ϫ/Ϫ mice and ceruloplasmindeficient Long-Evans Cinnamon rats, which have hepatic iron-and copper-loading, suffer only mild hematological disturbances (10,11,40).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All of these observations are consistent with the model that copper status can modulate iron release due to the metal's regulation of FPN1 gene expression. This model is also consistent with the observations that copper-deficient rodents, which have ironloaded but copper-depleted livers, display profound microcytic anemia (5, 6), whereas Cp Ϫ/Ϫ mice and ceruloplasmindeficient Long-Evans Cinnamon rats, which have hepatic iron-and copper-loading, suffer only mild hematological disturbances (10,11,40).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this model, ceruloplasmin knockout mice store excess iron in liver and the reticuloendothelial system (10). However, the absence of ceruloplasmin activity does not fully explain the function of copper in iron release because these animals display only very mild iron deficiency anemia (11). Moreover, aceruloplasminemic patients who inherit loss-of-function mutations in the ceruloplasmin gene are also only slightly anemic (12).…”
mentioning
confidence: 86%
“…21,22 The primer pairs used for quantification of specific mRNAs are listed in Table 1 and were in part described previously. [23][24][25] Liver iron analysis Total iron in the liver tissues was determined by flame atomic absorption spectroscopy under alkaline conditions on a Varian SpectrAA220 spectrometer (Varian, Zug, Switzerland) following solubilization by tetramethylammonium hydroxide. 26…”
Section: Quantitative Reverse Transcriptase-polymerase Chain Reactionmentioning
confidence: 99%
“…21,22 The primer pairs used for quantification of specific mRNAs are listed in Table 1 and were in part described previously. [23][24][25] …”
Section: Quantitative Reverse Transcriptase-polymerase Chain Reactionmentioning
confidence: 99%
“…However, Williams and co-workers (46) showed that the ferroxidase activity of Cp varies widely between species, being lowest in the rat and 10-fold higher in swine, which led the authors to conclude that this action may not be the major function of Cp but that it only enhances the export of iron. Certainly, intact Cp is necessary for the export of iron, because iron accumulated in the liver of individuals with aceruloplasminemia and in Cp knockout mice (18,47).…”
mentioning
confidence: 99%